2014
DOI: 10.1111/j.1751-908x.2014.00302.x
|View full text |Cite
|
Sign up to set email alerts
|

CAMAM: A Miniature Laser Ablation Ionisation Mass Spectrometer and Microscope‐Camera System for In Situ Investigation of the Composition and Morphology of Extraterrestrial Materials

Abstract: Performance studies of a microscope‐camera system (MCS) and a laser ablation/ionisation mass spectrometer (LIMS) instrument (referred to here as a laser mass spectrometer or LMS) are presented. These two instruments were designed independently for in situ analysis of solids on planetary surfaces and will be combined to a single miniature instrument suite for in situ chemical and morphological analysis of surface materials on planetary bodies. LMS can perform sensitive chemical (elemental, isotope and molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 59 publications
2
58
0
Order By: Relevance
“…1). The measurement campaigns were realized in a sequential measurement procedure [by homemade software for the control of the acquisition system, micro translational stages, and laser system (Riedo, 2014;Tulej et al, 2014)], including, first, the positioning of the micro translational stage to the desired surface location and the subsequent analysis by laser mass spectrometry. The calibration of the x-y-z stages with the x-y coordinates of the sample could be set with an accuracy of about -10 lm.…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…1). The measurement campaigns were realized in a sequential measurement procedure [by homemade software for the control of the acquisition system, micro translational stages, and laser system (Riedo, 2014;Tulej et al, 2014)], including, first, the positioning of the micro translational stage to the desired surface location and the subsequent analysis by laser mass spectrometry. The calibration of the x-y-z stages with the x-y coordinates of the sample could be set with an accuracy of about -10 lm.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Detection of elements and their isotopes to differentiate between biotic an abiotic materials can be investigated by currently available miniature mass spectrometric instruments (Brinckerhoff et al, 2000;Rohner et al, 2003Rohner et al, , 2004Managadze et al, 2010). Performance studies of a miniature laser ablation/ionization time-of-flight mass spectrometer (LMS) system developed for space research in our group have been reported in several recent publications (Riedo et al, 2010(Riedo et al, , 2013a(Riedo et al, , 2013bTulej et al, , 2014Neuland et al, 2014;Grimaudo et al, 2015). Laser ablation/ionization mass spectrometry allows for highly sensitive detection of almost all elements and isotopes with their concentrations down to tens of parts per billion at significantly better than unit mass resolution.…”
Section: Introductionmentioning
confidence: 99%
“…The remote access to these units allows measurements with specific needs to be conducted, such as single spot measurements or rastering over a complete sample surface stepwise or continuously, including the acquisition of single laser shot mass spectra. [4,13,17,23,32,36] …”
Section: Fig 2 Composite Microscope Image Of Anmentioning
confidence: 99%
“…[26] Unfortunately, the lander platform was cancelled later on due to budgetary reasons but since its first design in 2003 LMS has been continuously further developed. [4,13,17,[32][33][34][35][36][37][38][39][40][41][42] Today, LMS represents the most powerful and versatile LIMS system ever designed for in situ space investigations and exhibits top performing figures of merit. The system has the capability to conduct quantitative measurements with high detection sensitivity (10 ppb, atomic fraction) and with a dynamic range of about eight orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation